Machine tool component manufacturing – a lean approach. (1st January 2012) - John, B.; Selladurai, V.; Ranganathan, Rajesh
This paper presents the application of lean manufacturing concept in the production of machine tools. Normally, lean principles are applied in the production of discrete parts, which are produced in large quantities and variety. But in machine tools, the production volume is comparatively low and variety is high. The machining operations and the cycle time required for the machining of major components of machine tools are normally high. In this paper, the manufacturing of main structure for the conventional high precision, centre lathe using cellular manufacturing is dealt with in detail. Traditionally, a process-type layout or a group technology layout is adopted in the manufacturing of lathe components. Both the methods have inherent problems and hence, the new method using lean manufacturing tools is introduced. The case study of a turning machine manufacturing company is considered for the detailed analysis. The performance improvements achieved through lean manufacturing is converted into mathematical equations and is optimised. The methodology described in this paper includes mathematical formulae that balance the work being performed to optimise the production resources necessary to achieve customer demand.